Therapeutic enhancement of radiation and immunomodulation by gold nanoparticles in triple negative breast cancer. Issue 2 (1st February 2021) - Janic, Branislava; Brown, Stephen L.; Neff, Ryan; Liu, Fangchao; Mao, Guangzhao; Chen, Yalei; Jackson, Latoya; Chetty, Indrin J.; Movsas, Benjamin; Wen, Ning
ABSTRACT: Gold nanoparticles (AuNPs) have been shown to enhance cancer radiotherapy (RT) gain by localizing the absorption of radiation energy in the tumor while sparing surrounding normal tissue from radiation toxicity. Previously, we showed that AuNPs enhanced RT induced DNA damage and cytotoxicity in MCF7 breast cancer cells. Interestingly, we found that cancer cells exhibited a size-dependent AuNPs intracellular localization (4 nm preferentially in the cytoplasm and 14 nm in the nucleus). We extended those studies to an in vivo model and examined the AuNPs effects on RT cytotoxicity, survival and immunomodulation of tumor microenvironment (TME) in human triple negative breast cancer (TNBC) xenograft mouse model. We also explored the significance of nanoparticle size in these AuNPs' effects. Mice treated with RT and RT plus 4 nm or 14 nm AuNPs showed a significant tumor growth delay, compared to untreated animals, while dual RT plus AuNPs treatment exhibited additive effect compared to either RT or AuNPs treatment alone. Survival log-rank test showed significant RT enhancement with 14 nm AuNP alone; however, 4 nm AuNPs did not exhibit RT enhancement. Both sizes of AuNPs enhanced RT induced immunogenic cell death (ICD) that was coupled with significant macrophage infiltration in mice pretreated with 14 nm AuNPs. These results showing significant AuNP size-dependent RT enhancement, as evident by both tumor growth delay and overall survival, reveal additional underlying immunological mechanisms and provide a platform for studying RT multimodal approaches for TNBC that may be combined with immunotherapies, enhancing their effect.